2021
DOI: 10.1016/j.rinp.2021.104658
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a stochastic delay differential model for COVID-19 infection with asymptomatic infected and interacting people: Case study in the UAE

Abstract: Public health science is increasingly focusing on understanding how COVID-19 spreads among humans. For the dynamics of COVID-19, we propose a stochastic epidemic model, with time-delays, Susceptible-Infected-Asymptomatic-Quarantined-Recovered (SIAQR). One global positive solution exists with probability one in the model. As a threshold condition of persistence and existence of an ergodic stationary distribution, we deduce a generalized stochastic threshold . To estimate the percentages of people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 31 publications
(29 reference statements)
0
28
0
Order By: Relevance
“…with initial values x(0) > 0, l(0) > 0, y(0) > 0, v(0) > 0, w(0) > 0. l(t) denotes the concentrations of infected cells in latent stage at t. m be the death rate of l(t) and latent infection become productively infected cells at the rate γ. 3,4,5). We define the basic concepts of probability theory and SDEs.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…with initial values x(0) > 0, l(0) > 0, y(0) > 0, v(0) > 0, w(0) > 0. l(t) denotes the concentrations of infected cells in latent stage at t. m be the death rate of l(t) and latent infection become productively infected cells at the rate γ. 3,4,5). We define the basic concepts of probability theory and SDEs.…”
Section: Model Formulationmentioning
confidence: 99%
“…Mathematical models have been introduced to define the within-host dynamical behaviors of various viral infections, mainly focusing on virus-to-cell spread in the bloodstream, such as human immunodeficiency virus (HIV) [1], COVID-19 [2,3], hepatitis C virus (HCV) [4,5], hepatitis B virus (HBV) [6], human T cell lymphotropic virus I (HTLV-1) [7], etc. Those classical viral infection models are composed of interactions among susceptible cells, infected target cells, and free viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in epidemiological research revealed that applying non-integer order differential equations is vital in obtaining good results for dynamical systems. The classical mathematical models of the integer-order derivatives have been greatly employed in studying infectious diseases [10] , [11] , [12] , [13] , [16] , [17] , [18] , [19] , [47] , [27] , [28] , [23] , [24] , [25] . For instance, Omame et al [9] considered and analyzed an integer-order model for the dynamics of Human papillomavirus and Chlamydia trachomatis using optimal control.…”
Section: Introductionmentioning
confidence: 99%
“…The studies focussed on different dynamics of the disease. For a new update about modeling in fractional calculus, we refer to [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%